Ethics: Light from the Golden Quartet - CHAKRABORTY, SK (JOURNAL OF HUMAN VALUES 11:1 (2005), 2005)
This article comprises deep structure clues to ethical issues in our lives drawn from the wisdom writings of Tagore, Vivekananda, Gandhi and Aurobindo. All of them had recognized frankly the negative tendencies of man-as-he-is. This fault at the base needs systematic correction and restoration. For, the positive spiritual potential of man-as-he-could-be requires a fault-free baseline as the runway. All of them readily accept the classical word `character' as signifying such a base. Illustrations from various walks of life, small or big, have been interspersed in the article to indicate the essential connections of principle to reality. It is hoped that we might consent to draw sustenance for ethics from our very roots despite inevitable failures or slippages. Ethics is too precious to gain or preserve without persistent battles with one's own self. Codes and laws are but thin layers of icing on the ethical cake.